2017
DOI: 10.1055/s-0037-1612598
|View full text |Cite
|
Sign up to set email alerts
|

A De Novo Xp11.23 Duplication in a Girl with a Severe Phenotype: Expanding the Clinical Spectrum

Abstract: The Xp11.22-p11.23 duplication syndrome was described in 2009 by Giorda et al and is characterized by intellectual disability, speech delay, and electroencephalography anomalies. We report a case of a 23-month-old girl who presented with epilepsy and global developmental delay and who had a small duplication at Xp11.23. The case we present here is the first case showing the clinical features of Xp11.22-p11.23 duplication syndrome only involving synovial sarcoma, X breakpoint ( ) genes: , , , and . This case re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Our most noteworthy observation on Patient 1 refers to her OFC (below the 3rd percentile). As far as we know, only two girls has been reported to date with OFC < 3rd percentile (Patient 2 at Edens et al, 2011;Arican et al, 2018). In addition, the mother of Giorda's Patient 1 should be mentioned with the same OFC value.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our most noteworthy observation on Patient 1 refers to her OFC (below the 3rd percentile). As far as we know, only two girls has been reported to date with OFC < 3rd percentile (Patient 2 at Edens et al, 2011;Arican et al, 2018). In addition, the mother of Giorda's Patient 1 should be mentioned with the same OFC value.…”
Section: Discussionmentioning
confidence: 96%
“…Non-recurrent duplications of 0, 3-55 Mb in size have been reported in addition to the recurrent form of about 4.5 Mb, therefore the genes involved in the individual patient's duplications may be quite different. Patients with this copy number alteration, which have become known so far, show surprisingly similar symptoms despite the variability in CNV size: the resulting symptoms do not correlate with size and gene content of the affected genomic regions (Giorda et al, 2009;Zou and Milunsky, 2009;Flynn et al, 2011;Arican et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Duplicated synaptophysin (SYP) codes a protein of the synaptic vesicle membrane and mutations have been associated with ID and epilepsy (10). Pinar et al in 2018 (11) reported a small duplication of only SSX1, SSX9, SXX3 and SXX4 at Xp11.23 in a 23-month-old girl with epilepsy and global developmental delay. The patient had very severe ID and died at 25 months of age from severe pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…CMA for discovery of copy number variants (CNVs) is now recommended as a first-line diagnostic tool in patients with unexplained DD/ID and ASD. 4,5 CMA provides a high-resolution genome-wide scan of genomic CNVs such as microdeletions and microduplications. The ability of generating high-resolution genomic data also leads to difficulties in determining CNVs' clinical significance.…”
Section: Introductionmentioning
confidence: 99%